Difference and proliferation: race in the poetry of Elizabeth Bishop - DOI: 10.4025/actascilangcult.v32i1.6154 - Caesar, Terry (Acta Scientiarum. Language and Culture, 2009)
The current paper deals with the whole imagination of race in the work of a major American poet. The very subject of race intersects with the question of national identity, also neglected in Bishop’s work, although not in the same way. The aim of the discussion is to align the racial text with the national text. How can we understand Bishop’s consistent interest in race throughout her poetry, and what effect can be observed in it as a result of her exposure to racial constructs in Brazil that are so different from those of her native United States? We can see this effect manifest even in the controversy over her 1965 magazine article on the quatercentenary of Rio de Janeiro. What does this controversy demonstrate, finally, but that national experience with respect to race turns out to be mutually exclusive? One cannot be in this respect both Brazilian and American—in prose. In poetry, however, it is quite another matter. The subject of race is all of a piece, and has been all along conducted in Bishop’s work according to a logic ultimately apart from national construction.